Development of agricultural insurance in the system of state support of the agricultural market - Ignatenko, Valentin (Global Prosperity, 2022)
The article examines the peculiarities and problems of the development of agricultural insurance in the system of state support for the agricultural market. Identified vectors of state support for the development of the agricultural sector in Ukraine and the place of agricultural insurance. The algorithm for the development of agricultural insurance in the system of state support for the agricultural market is substantiated, which is proposed to be implemented in three directions: 1) comprehensive promotion of the growth of mutual trust between agricultural insurance subjects; 2) settlement of consolidated liability among participants in the insurance process on the agricultural market; 3) determination of the conditions for the functioning of an effective insurance environment on the agricultural insurance market. The strategic directions of the development of agricultural insurance in the system of state support of the agricultural market are defined on the basis of systematic coordination of the actions of agricultural market subjects (direct: insurers, policyholders and intermediaries; indirect (state and non-state institutions), proper infrastructural and information support, management of transaction costs of insurance companies). The key condition for the effective interaction of all participants in the agricultural market is to promote the development of agricultural insurance in the system of state support. To ensure the sustainability of the development of agricultural insurance in the agricultural market, it is advisable to carry out its modernization, which is focused on the systematic implementation of strategic measures to maintain a favorable insurance environment in the agricultural market.